KEPEMIMPINAN KEPALA MADRASAH DALAM NENINGKATKAN MUTU MADRASAH DI MTS MUHAMMADIYAH KARANGKAJEN - Hendra Mahardika; Suyatno Suyatno; Achadi Budi Santosa (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
The quality of madrasah has a great impact on education in madrasas, that the quality of madrasah will have an impact on student learning outcomes, student competence, competence of madrasah teachers and education personnel, students' readiness to face the future, improving the quality of madrasah resources, learning environment, and learning community environment, and having an impact on a transformation of human resources for the welfare and competitiveness of the nation. This is a background for research and also a research objective, where researchers research on the leadership of school principals in improving quality in madrasas. The research method used by the researcher is descriptive qualitative research, with observational data collection, in-depth interviews and literature studies, and for data validation using source triangulation. All educational policies and practices are governed by a commitment to the vision and mission of the institution as the cornerstone of the strategy, and the focus on improving the learning process and teacher performance places teachers as the main partner in quality transformation. Data-driven program development, effective resource allocation, and participatory, evidence-based decision-making ensure that efforts to improve quality are not only outstanding but also practical and sustainable. This management ability is known as management ability. The foundation for quality improvement is complemented by the role of the school committee as a strategic partner, student achievement as a representation of the success of the system, and the availability of adequate facilities. Madrasah heads must not only have technical and visionary abilities, but they must also be able to build a culture of professionalism, control changes in relationships between stakeholders, and encourage continuous capacity building.